Mechanical Properties of Low Alloy High Phosphorus Weathering Steel - SAHOO, GADADHAR; JENA, BASANT KUMAR; GUPTA, NANDITA; SINGH, BALBIR (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
Mechanical behaviour of two low alloy steels (G11 and G12) was studied with respect to different phosphorus contents. Tensile strength and yield strength increased while % of elongation at failure decreased on increasing phosphorus content. The SEM photomicrograph of low phosphorus steel (G11) revealed ferrite pearlite microstructure. The highest phosphorus content (0.42 wt. % P) sample (G12) exhibited larger ferritic grain. The Charpy V notch (CVN) impact energy of G11 and G12 steel at room temperature was 32 J and 4 J respectively and their fractographs revealed brittle rupture with cleavage facets for both the steels. However, the fractograph of G11 steel after tensile test exhibited ductile mode of fracture with conical equiaxed dimple while that of G12 steel containing 0.42 wt. % P exhibited transgranular cleavage fracture. Based on this study, G11 steel containing 0.25 wt. % P could be explored as a candidate material for weathering application purpose where the room temperature toughness requirement is 20 J and 27 J as per IS 2062.
Keywords: Strengths; Steel; phosphorus; mechanical properties